ANALISIS PENGARUH LABA AKUNTANSI DAN LABA TUNAI TERHADAP DEVIDEN KAS PERUSAHAAN YANG TERDAFTAR PADA INDEKS LIQUID 45 - Febriati; Nurhakim, M. Asmal (Program Studi Akuntansi Universitas Panca Bhakti, 2022)
This study aims to determine the effect of accounting earnings and cash earnings on cash dividendsof companies listed on the Liquid 45 Index. The population in this study were all companies listedon the Liquid 45 Index and the sample of this study was 72 samples for three years of observation.The sampling technique used is purposive non-random sampling. Data collection in this study is touse the company's annual financial statements. There are several research methods used in thisstudy including the classical assumption test consisting of normality test, multicollinearity test,heteroscedasticity test, autocorrelation test and hypothesis testing consisting of multiple linearregression analysis, t test (partial test), f test (test simultaneous), and the coefficient of determination(Adjusted-R2). The results of this study indicate that accounting profit and cash profit have asignificant positive effect on cash dividends of companies listed on the Liquid 45 Index.